Conservação frigorificada de pitaia orgânica irradiada - Fernandes, Luiza Maria de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This work's objective was to evaluate the influence of different dosages of ionizing irradiation with 60Co in physical, physico-chemical, biochemical and chemical characteristics in post-harvest pitaya organic fruit of the Hylocereus undatus species, grown in the region of Itajobi - SP. The experiment was conducted in the Fruit and Vegetable Laboratory, Department of Agribusiness Management and Technology - FCA and Laboratory of Chemistry and Biochemistry, Department of Botany - IBB / UNESP - Botucatu - SP from March to April 2010. The radiation process was carried out at the Institute of Energy and Nuclear Research (IPEN) located in Sao Paulo. The fruits were harvested on the third day after the onset of color, selected, washed in running water and dried on paper towels. 20 fruits were, then, chosen, forming two replications of 10 fruits each, for characterization purposes without the interference of radiation and storage time. For treatments procedures, the fruits were packed in styrofoam trays, covered with PVC film, pre - cooled (8 ± oC for 24 hours) and subjected to different dosages of gamma irradiation (0.0, 0.2, 0.4; 0.6, 0.8 and 1.0 kGy of cobalt-60), and were subsequently stored in cold temperature of 8 ± 1 °C, with 90 ± 5% R U. The fruits were evaluated for their pH, soluble solids (SS), titratable acidity (TA), ratio (SS / TA), weight loss, respiratory activity, firmness, moisture, peel pulp relation, reducing sugars, non-reducing sugar, total sugars, phenolic compounds, flavonoid, protein, fiber, lipids and minerals on the day of the harvest for characterization and the results obtained were regarded as standard. After application of ionizing irradiation dosages, the fruits were evaluated after 0, 5, 10, 15 and 20 days of storage at a temperature of 8 ± 1 ºC for their pH, soluble solids (SS), titratable acidity (TA), ratio (SS / TA), weight loss, respiration rate, firmness ...

Objetivou-se avaliar a influência de diferentes doses de irradiação ionizante com o 60Co nas características física, físico-químicas, químicas e bioquímicas em pós-colheita de frutos de pitaia orgânica da espécie Hylocereus undatus, cultivada na região de Itajobí - SP. O experimento foi conduzido no Laboratório de Frutas e Hortaliças do Departamento de Gestão e Tecnologia Agroindustrial - FCA e Laboratório de Química e Bioquímica do Departamento de Botânica - IBB /UNESP - Botucatu - SP no período de março a abril de 2010. O processo de radiação foi realizado no Instituto de Pesquisas Energéticas e Nucleares (IPEN) localizado em São Paulo. Os frutos foram colhidos no terceiro dia após o início da coloração, selecionados, lavados em água corrente, secos em papel toalha. Destes foram considerados para fins de caracterização sem a interferência da radiação e tempode armazenamento, 20 frutos formando 10 repetições compostos por dois frutos cada. Para constituição dos tratamentos, os frutos foram embalados em bandejas poliestireno expandido, revestidas por filme de PVC, pré - resfriados (8oC por 24 horas) e submetidos as diferentes doses de irradiação gama (0,0; 0,2; 0,4; 0,6; 0,8 e 1,0 kGy de cobalto-60) sendo posteriormente armazenados em câmara fria a temperatura de 8 ± 1oC, com 90 ± 5% UR. Os frutos foram avaliados quanto ao pH, sólidos solúveis (SS), acidez titulável (AT), ratio (SS/AT), perda de massa, atividade respiratória, firmeza, umidade, relação polpa casca, açúcares redutores, açúcar não redutor e açúcar total, compostos fenólicos, flavonóides, proteína, fibra, lipídeos e minerais no dia da colheita, para caracterização dos frutos e os resultados obtidos foram considerados como padrão. Após a aplicação das doses de irradiação ionizante os frutos foram avaliados nos tempos 0, 5º, 10º, 15º e 20º dias de armazenamento ...
Keywords: Frutas - Cultivo; Frutas - Fisiologia; Pós-colheita; Frutas - Conservação; Fruit Physiology